Academic stress and associated sociodemographic variables: A study of pre-university students in Karnataka, India - Shreemathi S Mayya; Arun Mayya; Maxie Martis; R Vani Lakshmi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Academic stress is a predominant phenomenon among grade 11 and 12 students. The performance in Grade 12 is important for entry to higher education programs in India. The purpose of the study was to assess the magnitude of the perceived academic stress and identify the main stressors and the sociodemographic variables associated with the perceived academic stress among adolescents enrolled in the science stream in coastal Karnataka. MATERIALS AND METHODS: Upon Institutional Ethical Committee approval, a cross-sectional survey was carried out among pre-university students (science stream) of coastal Karnataka during February-April 2021. The study used Manipal Inventory of Academic Stress (MIAS) scale to collect data on perceived academic stress from 1859 students (response rate 68.3%). Stratified cluster sampling method was used to collect data from the study participants. IBM Statistical Package for the Social Sciences (SPSS) 26.0 was used to analyze the data. Descriptive statistics, unpaired t-test, one-way analysis of variance (ANOVA), and multiple linear regression analyses were used to study the association between academic stress and various demographic variables. RESULTS: The study revealed that 28% of the Grade 11 students and 26% of the Grade 12 students experienced high or extreme stress. The significant stressors were lack of time for revision, queries from neighbors or relatives, and parental expectations on academic performance. Gender, residence, and the medium of instruction until Grade 10 were associated with academic stress. CONCLUSION: Measures at the institutional and national levels are necessary to reduce the academic stress in higher secondary education. The integrated curriculum proposed in the National Educational Policy 2020 addresses a few stressors identified in this study.